Prevalence of offering menopause hormone therapy among primary care doctors and its associated factors: a cross-sectional study - Low, Tiong Lim; Cheong, Ai Theng; Devaraj, Navin Kumar; Ismail, Rohayah (Public Library of Science, 2024)
Background Guidelines recommend Menopausal Hormone Therapy (MHT) as the most effective treatment for menopausal symptoms. However, a local study found that the usage of MHT among menopausal women was low (8.1%), with one of the main reasons being it is not recommended by doctors. Therefore, the objectives of this study are to determine the prevalence of offering MHT in treating symptomatic menopausal women among primary care doctors (PCDs) and its associated factors. Methods This cross-sectional study involved PCDs from the Federal Territory of Kuala Lumpur, the Federal Territory of Putrajaya and the state of Selangor. All PCDs provided services in government primary care clinics from the three states were invited through the doctor in charge of each clinic. An online survey links was provided for the participants to the self-administered questionnaire. The questionnaire included PCDs’ demographics, their menopause management practices, attitudes towards MHT, perceived barriers in offering MHT, knowledge of related guidelines and received training on menopause management. The outcome variable was offering MHT which defined as either prescription of MHT or referral to hospital for MHT initiation. Multivariate logistic regression analysis was performed to determine the factors associated with offering MHT. Results The response rate was 42.9% (559/1301). Of those who participated in the study, 77.8% of PCDs were female and 89.1% were medical officer. Although 66.9% of the participants reported offering MHT to their patients, the actual prescription rate was low (0.9%). Most PCDs (66%) would refer the patients to hospitals. 87.1% of PCDs (487/559) reported that MHT was not available in their clinic. In the past 12 months, 83% of PCDs had not received any related training. Female PCDs (AOR:2.5, CI: 1.51–4.13, p<0.001), perceiving MHT as preference treatment for menopause symptom (AOR:3.6, CI: 2.13–6.19, p < 0.001), having likelihood to recommend MHT to family and friends (AOR:3.0, CI: 1.87–4.83, p < 0.001), and receiving training on menopause management (AOR:2.7, CI: 1.30–5.56, p = 0.008) were the positive predictor of offering MHT. The negative predictors in offering MHT were no-experience in prescribing MHT (AOR: 0.4, CI: 0.15–0.87, p = 0.024) and lack of information regarding MHT for the patient (AOR: 0.4, CI:0.20–0.67, p < 0.001). Conclusion The study revealed a low rate of MHT prescription among PCDs, with many relying on referrals to hospitals for managing menopausal symptoms. The findings underscore the need for strategies that includes fulfilling professional training gaps, improving MHT availability, and improving information dissemination for patient. © 2024 Low et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.